Metaphors of victory and defeat in sports headlines in English and Spanish - Sara Quintero Ramírez (Revista de Lingüística y Lenguas Aplicadas)
Metaphor is one of the most frequently used resources in the specialized language of sports (cf. Segrave, 2000; Herráez Pindado, 2004; Segura Soto, 2009; Medina Montero, 2015). The focus of this study is on how victory and defeat are expressed through metaphors in sports headlines. The data collection consists of 100 sports headlines in English and 100 in Spanish. Based on our findings, we argue that there is a diversity of metaphors that take advantage of mutual semantic fields to present victory and defeat in the two corpora, the semantic fields that were identified in the study are: a) war, b) laws, c) cleaning, d) royalty, e) life and death, f) space and g) pain. Finally, when a team’s nickname is an animal-related name, journalists map the properties of the animal onto the team (Silaški, 2009) to make the headline more attractive for the audience.